Triggered ferroptotic albumin-tocopherol nanocarriers for treating drug-resistant breast cancer - Gao, Qianqian; Liu, Tingting; Sun, Li; Yao, Yongliang; Li, Fang; Mao, Lingxiang (Frontiers in Oncology, 2024)
Ferroptosis is considered an effective method to overcome drug-resistant tumors. This study aims to use three FDA-approved biological materials, human serum albumin, D-α-tocopherol succinate, and indocyanine green, to construct a novel biocompatible nanomaterial named HTI-NPs, exploring its effect in drug-resistant breast cancer (MCF-7/ADR cells). The research results indicate that HTI-NPs can selectively inhibit the proliferation of MCF-7/ADR cells in vitro, accompanied by upregulating transferrin receptor, generating reactive oxygen species, and downregulating glutathione peroxidase 4. Under laser irradiation, HTI-NPs can promote ferroptosis by inhibiting glutathione expression through photodynamic therapy. Notably, HTI-NPs exhibit good inhibitory effects on MCF-7/ADR xenograft tumors in vivo. In conclusion, HTI-NPs represent a biocompatible nanomaterial that induces ferroptosis, providing new insights and options for treating drug-resistant breast cancer.